2020
DOI: 10.3892/ijo.2020.5004
|View full text |Cite
|
Sign up to set email alerts
|

TRIM22 inhibits endometrial cancer progression through the NOD2/NF‑κB signaling pathway and confers a favorable prognosis

Abstract: Endometrial cancer (EnC) is a malignant gynecological tumor commonly observed in developed countries, specifically among post-menopausal women. Although numerous patients with EnC receive promising prognoses, those with advanced or metastatic disease often have a poor prognosis and an impaired quality of life. Tripartite motif-containing 22 (TRIM22) has been confirmed to play many crucial roles in different biological processes, from inflammatory to tumorigenesis. However, the multifaceted roles of TRIM22 in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…It is confirmed that the TRIM22 played many crucial roles in different biological processes, from inflammatory to tumorigenesis. In endometrial cancer, TRIM22 is proven to inhibit tumor growth by NF-κB signaling pathway, and conferred a favorable prognosis ( 44 ). CIITA is the regulator of the major histocompatibility complex gene expression ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is confirmed that the TRIM22 played many crucial roles in different biological processes, from inflammatory to tumorigenesis. In endometrial cancer, TRIM22 is proven to inhibit tumor growth by NF-κB signaling pathway, and conferred a favorable prognosis ( 44 ). CIITA is the regulator of the major histocompatibility complex gene expression ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four TRIM proteins have been related to EC: TRIM22, TRIM25, TRIM27 and TRIM44 [ 157 , 158 , 159 , 160 , 161 , 162 ]. TRIM22 expression was reported to be downregulated in EC samples compared to normal endometrial tissues, and low TRIM22 expression was found to be associated with a high clinical stage of the disease [ 157 ]. In the same study, TRIM22 decreased proliferation and migration of KLE, Ishikawa and RL-952 EC cells in vitro and inhibited tumor growth in xenograft models in vivo [ 157 ].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…TRIM22 expression was reported to be downregulated in EC samples compared to normal endometrial tissues, and low TRIM22 expression was found to be associated with a high clinical stage of the disease [ 157 ]. In the same study, TRIM22 decreased proliferation and migration of KLE, Ishikawa and RL-952 EC cells in vitro and inhibited tumor growth in xenograft models in vivo [ 157 ]. These effects are explained by increased levels of the Nucleotide-binding oligomerization domain-containing protein 2 (NOD2) protein upon TRIM22 overexpression in Ishikawa cells [ 157 ].…”
Section: Endometrial Cancermentioning
confidence: 99%
See 2 more Smart Citations